2018
DOI: 10.1016/j.jconrel.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-induced immunosuppression and tumor growth is mediated by macrophages and mitigated by liposome-encapsulated alendronate

Abstract: Liposomal nanoparticles are the most commonly used drug nano-delivery platforms. However, recent reports show that certain pegylated liposomal nanoparticles (PLNs) and polymeric nanoparticles have the potential to enhance tumor growth and inhibit antitumor immunity in murine cancer models. We sought herein to identify the mechanisms and determine whether PLN-associated immunosuppression and tumor growth can be reversed using alendronate, an immune modulatory drug. By conducting in vivo and ex vivo experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 73 publications
0
50
1
Order By: Relevance
“…Similarly, Sabnani et al and Rajan et al found that compared to the vehicle control (e.g., 5% dextrose solution, saline), empty pegylated liposomes accelerated the growth of subcutaneous TC-1 tumors in mice [109,112]. The accelerated tumor growth was attributed to diminished macrophage function and number of tumor-specific T cells [112], as well as a 66% decrease in M1-TAMs and a 100% increase in M2-TAMs [109]. Based on these results, strategies to overcome immunosuppression and tumor progression triggered by liposomes may potentially improve the efficacy of some liposomal anticancer drugs.…”
Section: Interactions With the Mononuclear Phagocyte Systemmentioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, Sabnani et al and Rajan et al found that compared to the vehicle control (e.g., 5% dextrose solution, saline), empty pegylated liposomes accelerated the growth of subcutaneous TC-1 tumors in mice [109,112]. The accelerated tumor growth was attributed to diminished macrophage function and number of tumor-specific T cells [112], as well as a 66% decrease in M1-TAMs and a 100% increase in M2-TAMs [109]. Based on these results, strategies to overcome immunosuppression and tumor progression triggered by liposomes may potentially improve the efficacy of some liposomal anticancer drugs.…”
Section: Interactions With the Mononuclear Phagocyte Systemmentioning
confidence: 83%
“…In an orthotopic ovarian carcinoma (ID8-VEGF-GFP) mouse model, La-Beck et al showed that empty liposomes increased tumor volume by over 3-fold and doubled the number of metastatic sites, compared to the vehicle control [107]. Similarly, Sabnani et al and Rajan et al found that compared to the vehicle control (e.g., 5% dextrose solution, saline), empty pegylated liposomes accelerated the growth of subcutaneous TC-1 tumors in mice [109,112]. The accelerated tumor growth was attributed to diminished macrophage function and number of tumor-specific T cells [112], as well as a 66% decrease in M1-TAMs and a 100% increase in M2-TAMs [109].…”
Section: Interactions With the Mononuclear Phagocyte Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…Other pioneer studies unexpectedly discovered that dendrimer nanoparticles improved disease scores in animal models of granulomatous, autoimmune, and edema diseases ( 116 ). Another example illustrating the immunosuppressive properties of nanoparticles is the study by Rajan ( 117 ). Liposomal nanoparticles possess the ability to elicit an immunosuppressive cell environment that subsequently suppress anti-tumor immunity and favor tumor progression.…”
Section: Nanoparticles Induce Immunosuppressionmentioning
confidence: 99%
“…Liposomes are the most successful drug delivery nano-carriers for tumor targeted drug delivery (Rajan et al., 2017 ) through the enhanced permeability and retention (EPR) effect (Maeda, 2001 ). To improve the degree of internalization to cancer cells, specific ligand-anchored liposomes have been explored which can be specifically recognized by cancer cells through their over-expressed receptors, for example, the estrogen receptors (Wicki et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%